(untitled) (International Journal of Medical and Surgical Sciences, 2016)
The inferior alveolar nerve (IAN) injury to remove the third molars is often caused by the intimate relationship between the nerve and the roots of the teeth. Coronectomy technique or intentional root retention, may minimize this problem. Thirty patients underwent coronectomy in 30 third molars with follow up of at least 6 months. Coronectomy technique deliberately protected the lingual nerve as part of the surgical procedure. All roots were at least 3 mm below the buccal and lingual bony walls. All patients were radiographed preoperatively, immediately postoperatively, and after 6 months. There were no cases of IAN damage involved in this study of 30 patients who underwent 30 coronectomies. There was one case of transient lingual nerve involvement, probably by the use of lingual retractor. One patient required subsequent removal of the roots of both lower third molars, due to lack of healing, and one patient required subsequent removal of a root cause of migration back to the surface. migration of the roots was observed in approximately 30 % of patients during a period of six months. Coronectomy seems to be a viable technique in those cases where the removal of all tooth could put the IAN at considerable risk of damage. The technique appears to be associated with a low incidence of complications, but the subsequent migration of the roots can be a problem in the long term.